Adaptive reuse of parking in the cities of the future. Issue 1 (March 2020) - Malysheva, E; Generalova, E
Abstract: The article considers the problems of modern highly urbanized cities caused by the irrational development of transport infrastructure, emphasizes the need for sustainable transport systems. The problem of reducing the life cycle of automotive infrastructure (parking garages) is considered. The international experience of reconstruction and adaptation of parking lots is analyzed. Typological features of the design of parking lots with the possibility of their subsequent adaptation are revealed.